2008
DOI: 10.2220/biomedres.29.131
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cytoskeletal integrity in the regulation of Cl- and amylase secretion from rat parotid acinar cells

Abstract: The cytoskeleton serves as a signal modulator for Ca 2+ and cAMP-regulated cell functions including the secretion of ions and granule contents. The interaction between Ca 2+ and cAMP signaling systems potentiates amylase secretion and suppresses Cl − secretion in the parotid glands. In this study, we investigated the role of the cytoskeleton in the modulation of Cl − and amylase secretion from rat parotid acinar cells upon activation of each intracellular signaling system and their interaction. Cytochalasin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The polymerization and depolymerization of actin filaments generates direct forces that drive changes in cell shape and, together with molecular motors that move along the actin filaments and microtubules, guide the organization of cellular components . The disruption of microfilaments with cytochalasin B prevented amylase release in rat submandibular glands, which indicates that secretion of amylase depends on the integrity of microfilaments. , It has been reported that actin filament integrity was required for the activation of Cl − channels in rat parotid acinar cells . The optimal Na + /H + exchanger activity also requires the integrity of the cellular F-actin network in a hamster ovary cell line .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The polymerization and depolymerization of actin filaments generates direct forces that drive changes in cell shape and, together with molecular motors that move along the actin filaments and microtubules, guide the organization of cellular components . The disruption of microfilaments with cytochalasin B prevented amylase release in rat submandibular glands, which indicates that secretion of amylase depends on the integrity of microfilaments. , It has been reported that actin filament integrity was required for the activation of Cl − channels in rat parotid acinar cells . The optimal Na + /H + exchanger activity also requires the integrity of the cellular F-actin network in a hamster ovary cell line .…”
Section: Discussionmentioning
confidence: 97%
“…Of the cytoskeletal proteins, actin is a major structural element of cytoskeleton and is involved in saliva secretion. Alpha-actinin-4 is an actin-binding protein and is present in the perinuclear region of cytoplasm and nucleus and colocalized with actin stress fibers . Vimentin, keratin and lamin-A/C are components of intermediate filaments.…”
Section: Discussionmentioning
confidence: 99%
“…The Tukey's test was used to compare group means of current amplitudes using Mathematica software (Wolfram Research, Champaign, IL). Details of the devices used in patch‐clamp recordings have been previously described (Kongo et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In epithelial cells, α‐fodrin reorganization is believed to play an important role in secretion (Perrin et al , 1987), as it has been shown to inhibit phospholipases C, A2, and D in permeabilized HL‐60 cells (Lukowski et al , 1998). Cytochalasin D, an actin‐depolymerizing agent, suppresses CCh‐induced Cl − currents and forskolin‐induced amylase secretion in rat parotid acinar cells, suggesting that cytoskeletal integrity is also involved in the regulation of salivary secretion (Kongo et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of M3R increases the cytoplasmic‐free calcium concentration ([Ca 2+ ] i ), subsequently activating Ca 2+ ‐dependent K + and Cl − channels (Park et al , 2001; Melvin et al , 2005). Cytoskeletal integrity is also involved in the regulation of salivary secretion (Kongo et al , 2008). Stimulation of muscarinic receptors produces a reorganization of the α‐fodrin cytoskeleton in parotid acinar cells (Perrin et al , 1992).…”
Section: Introductionmentioning
confidence: 99%